2019
DOI: 10.1002/cctc.201901488
|View full text |Cite
|
Sign up to set email alerts
|

Combining STM, RAIRS and TPD to Decipher the Dispersion and Interactions Between Active Sites in RhCu Single‐Atom Alloys

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 60 publications
5
50
0
Order By: Relevance
“…Because the CO adsorption geometry remains upright, the change in site preference produces well separated C-O stretch bands in RAIRS that may be used to identify the presence of monomers vs. dimers of the minority metal component. 9,12,57 Our results suggest that an analogous characterization of Ti ensembles in the Ti-Cu(111) alloy is less feasible using CO RAIRS. We thus emphasize that our CO RAIRS results do not provide direct information about Ti dimers or larger ensembles that may be present in the Ti-Cu(111) alloy and that other characterization methods (e.g., low temperature STM) or probe molecules are needed to identify such structures and quantify their concentrations.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Because the CO adsorption geometry remains upright, the change in site preference produces well separated C-O stretch bands in RAIRS that may be used to identify the presence of monomers vs. dimers of the minority metal component. 9,12,57 Our results suggest that an analogous characterization of Ti ensembles in the Ti-Cu(111) alloy is less feasible using CO RAIRS. We thus emphasize that our CO RAIRS results do not provide direct information about Ti dimers or larger ensembles that may be present in the Ti-Cu(111) alloy and that other characterization methods (e.g., low temperature STM) or probe molecules are needed to identify such structures and quantify their concentrations.…”
Section: Discussionmentioning
confidence: 85%
“…The preference for CO to adsorb in flat-lying geometries on contiguous Ti surface structures is distinct from the behavior of CO adsorbed on dilute alloys of Cu(111) with late transition metals (e.g., Ni, Rh, Pd, Pt), 9,12,57 and has consequences for characterizing Ti-Cu(111) surface alloys. For late transition metal dopants, CO adsorbs into an upright geometry irrespective of the metal ensemble size and exhibits a change in site preference from atop to bridge for isolated dopant atoms vs. larger ensembles.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…extended Ni(111). [30][31][32] Further evidence for the lower frequency of the IR feature on the SAA comes from our DFT calculations that put this frequency at 1991 cm -1 , which is reasonably accurate when taking into consideration inherent errors in DFT calculations.…”
Section: Resultsmentioning
confidence: 60%
“…Single-atom alloys (SAAs) [44][45][46][47][48] are a class of single-atom catalysts, in which an atomically active metal is generally dispersed in a less-active metal host, resulting in well-defined local coordination environments of active sites and unique catalytic properties from the individual components. [49][50][51][52][53][54][55][56] Currently, a number of studies focusing on SAA catalysts were reported in this field.…”
Section: Introductionmentioning
confidence: 99%